(untitled) (Zaporizhzhia Historical Review, 2021)
The activity of one of the prominent figures of the Russian Empire – Kirill Grigoryevich Razumovsky – is being explored. Basing of little known archive materials, the detailed biography of this Hetman and his role in political life of the XVIIIth century are being described.